A VOSviewer-Based Bibliometric Analysis of Prescription Refills - Fu, Runchen; Xu, Haiping; Lai, Yongjie; Sun, Xinying; Zhu, Zhu; Zang, Hengchang; Wu, Yibo (Frontiers in Medicine, 2022)
Purpose: Prescription refills are long-term prescriptions for chronic patients in stable status, which varies from country to country. Well-established prescription refill system is beneficial for chronic patients’ medication management and facilitates efficacy of clinical care. Therefore, we carried out a bibliometric analysis to examine the development of this field. Summary: Publications on prescription refills from 1970 to 2021 were collected in the Web of Science Core Collection (WoSCC). Search strategy TS=("prescri* refill*" OR "medi* refill*" OR "repeat prescri*" OR "repeat dispens*" ) OR TI=( refill*) was used for search. VOSviewer was applied to visualize the bibliometric analysis. A total of 319 publications were obtained in WoSCC. Study attention on prescription refills had shown a steady rise but still low in recent years. The USA was the most productive country, which had the highest total citations, most average citation of per publication and highest H-index, and participated in international collaboration most frequently. University of California system was the most productive institution. U.S. Department of Veterans Affairs was the institution with the most citation, most average citation, highest H-index, Sundell K.A. was the most productive author and Steiner J.F. was the most influential author. “Adherence”, “medication” and “therapy” were the most prominent keywords. Conclusion: Publications on prescription refills has increased rapidly and continued to grow. The USA had the leading position in the area. It is recommended to pay closer attention to the latest hotspots, such as “Opioids”, “Surgery”, “Differentiated care” and “HIV”.